Antioxidant activity and 1H NMR profiling of leaves and fruits of Rhodomyrtus tomentosa from South Kalimantan, Indonesia - EVI MINTOWATI KUNTORINI; LILING TRIYASMONO; MARIA DEWI ASTUTI (Society for Indonesian Biodiversity, 2024)
Abstract. Kuntorini EM, Triyasmono L, Astuti MD. 2024. Antioxidant activity and 1H NMR profiling of leaves and fruits of Rhodomyrtus tomentosa from South Kalimantan, Indonesia. Biodiversitas 25: 2020-2027. Rhodomyrtus tomentosa (Aiton) Hassk is a flowering plant belonging to Myrtaceae, native to southern and southeastern Asia. This study aims to evaluate and compare the antioxidant activity of leaves and fruits ethanol extracts of R. tomentosa (Ait.) Hassk from two locations, namely Banjar and Batola, South Kalimantan Province, Indonesia. The samples included old and young leaves and three stages of fruit maturity, namely green, red, and purple. 1H NMR spectroscopy was used to identify the chemical profile of extracts, which comprised organic acids, carbohydrates, amino acids, and phenolic compounds. Antioxidant capacity was assessed with DPPH, which showed intensity differences in aromatic shifts in leaves and fruits for both regions. Young leaves and green fruits had higher intensity than old leaves and red and purple fruits, correlating with antioxidant capacity. Analysis of 1H NMR spectra of young and old leaf extracts identified vital metabolites, such as gallic acid, myricetin 3-O-rhamnopyranoside, myricetin, quercetin, quercetin-3-O-glucoside, as well as syringic acid, in regional chemical shifts of 10.0-6.0 ppm as aromatic compound area. The differences in spectral signal intensity revealed higher metabolite levels, specifically carbohydrates and amino acids, in red and purple fruits. However, green fruits had higher quantities of aromatic compounds.